2021
DOI: 10.1088/2058-6272/abf72a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the electromagnetic effect and improvement of the plasma radial uniformity in a large-area, very-high frequency capacitive argon discharge

Abstract: We performed an experimental investigation on the electromagnetic effect and the plasma radial uniformity in a larger-area, cylindrical capacitively coupled plasma reactor. By utilizing a floating hairpin probe, dependences of the plasma radial density on the driving frequency and the radio-frequency power over a wide pressure range of 5–40 Pa were presented. At a relatively low frequency (LF, e.g. 27 MHz), an evident peak generally appears near the electrode edge for all pressures investigated here due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Due to continuous growth in both the driving frequency and the wafer size, plasma non-uniformities caused by the standing wave effect have become a major challenge in the material etching and film deposition processes. To optimize the plasma uniformity, several methods have been put forward, such as the use of specially shaped electrodes, [163][164][165][166][167] phase-shift control, [168][169][170] the use of the dual-frequency or multi-frequency source, [133,138,139,171,172] discharge symmetry control, [173,174] etc.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%
See 2 more Smart Citations
“…Due to continuous growth in both the driving frequency and the wafer size, plasma non-uniformities caused by the standing wave effect have become a major challenge in the material etching and film deposition processes. To optimize the plasma uniformity, several methods have been put forward, such as the use of specially shaped electrodes, [163][164][165][166][167] phase-shift control, [168][169][170] the use of the dual-frequency or multi-frequency source, [133,138,139,171,172] discharge symmetry control, [173,174] etc.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%
“…[168][169][170] This is the so-called "phase-shift control" method. Besides, the dual-frequency [138,139,171,172] or multi-frequency [133] source can be used as an alternative way to optimize the plasma uniformity. By using a two-dimensional plasma model, Bera et al [171] found that the plasma distribution can be effectively controlled by mixing VHF source powers at 60 MHz and 180 MHz.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 13, a short summary of uniformity analysis under four typical experimental conditions is shown as column chart. The uniform coefficient [57] is utilized for evaluating the plasma axial uniformity, which is calculated from the following equation:…”
Section: Uniformity Analysismentioning
confidence: 99%